Bronze Vessels with Over Vase Looped Handle of Capenate Manufacture (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2012)
In the work presented we attempted to clarify the particular bronze vascular forms herein defined recipienti troncoconici ad ansa sormontante (“over vase loop handled frustoconical vessels”), often called mug, caccabus or kettle. Through a morphological analysis of the bronze vessel we proposed a hypothesized purpose of infusion or sauce preparation or a spiced wine container. The contextual analysis made it possible to date the articles between the mid-third and half of the second century BC, although some clues can extend the upper limit toward the end of the fourth century BC. The data context also allowed to suggest the site of Capena as production centre, since 31 of the 67 specimens come from the neighboring necropoles.
Keywords: Capena; capenati; necropole; bronze vessels; mug; cacabus; kettle